Γδ T Cell-Based Immunotherapy in Melanoma: State of the Art. (23rd May 2019) - Toia, F.; Di Stefano, A. B.; Meraviglia, S.; Lo Presti, E.; Pirrello, R.; Rinaldi, G.; Fulfaro, F.; Dieli, F.; Cordova, A.
Abstract : Metastatic melanoma is still associated with a poor prognosis, and there is increasing interest in immunotherapy alone or in combination with other adjuvant therapies. Γ δ T lymphocytes play a pivot role in the immune response against cancer, but while γδ -based immunotherapy is already a clinical reality for several solid tumors, data on melanoma are still limited and fragmented. This systematic review presents preclinical and clinical evidence for a role of γδ T lymphocytes in immunotherapeutic strategies for advanced melanoma and discusses research state of the art and future perspectives. Current strategies focus on in vivo stimulation, and ex vivo adoptive therapy and vaccination; results are promising, but further studies are needed to better investigate the interactions in tumoral microenvironment and to improve clinical efficacy of immunotherapeutic protocols.